Potassium channels: Novel targets for tumor diagnosis and chemoresistance - Li, Meizeng; Tian, Peijie; Zhao, Qing; Ma, Xialin; Zhang, Yunxiang (Frontiers in Oncology, 2023)
In recent years, the role of potassium channels in tumors has been intensively studied. Potassium channel proteins are widely involved in various physiological and pathological processes of cells. The expression and dysfunction of potassium channels are closely related to tumor progression. Potassium channel blockers or activators present antitumor effects by directly inhibiting tumor growth or enhancing the potency of classical antitumor agents in combination therapy. This article reviews the mechanisms by which potassium channels contribute to tumor development in various tumors in recent years, introduces the potential of potassium channels as diagnostic targets and therapeutic means for tumors, and provides further ideas for the proper individualized treatment of tumors.